1989
DOI: 10.1080/03014468900000382
|View full text |Cite
|
Sign up to set email alerts
|

Heart-rate variation, age, and behaviour in elderly women

Abstract: Minute-by-minute heart-rate recordings over a period of 24 hours were obtained once for each of a group of 29 elderly women, 14 of whom lived in private accommodation, and 15 of whom lived in institutionalized homes for the aged. Activity diaries were kept on the subjects during the measurement period. A comparison of individual 24-hour profiles, diaries, and group averages was made. Strong positive correlations were found in both groups between average waking and sleeping heart-rates, and between the standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…This was found, for example, for female residents of homes for the aged [9] and assisted care facilities [10], who were more sedentary than their community-dwelling counterparts. Women living independently were engaged in more active activities, such as household work, while institutionalized women spent more time in seated activities, such as reading [9]. When both genders were included, also less activity was recorded in residents of aged care facilities than in the older adults who lived independently [11].…”
Section: Introductionmentioning
confidence: 98%
“…This was found, for example, for female residents of homes for the aged [9] and assisted care facilities [10], who were more sedentary than their community-dwelling counterparts. Women living independently were engaged in more active activities, such as household work, while institutionalized women spent more time in seated activities, such as reading [9]. When both genders were included, also less activity was recorded in residents of aged care facilities than in the older adults who lived independently [11].…”
Section: Introductionmentioning
confidence: 98%
“…In spite of these limitations, this study provides qualitative evidence that modified Taekwondo can be instrumental in promoting health benefits among nursing home residents. As indicated, the nursing home residents experience higher prevalence of physical inactivity and of psychological problems and concerns than older adults who are living independently in their communities [ 37 – 39 ]. The results of this study indicate that modified Taekwondo can be used as an intervention to increase the physical activity participation and ameliorate negative psychological consequences associated with confinement to nursing homes.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the percentage of older adults that meets the recommended physical activity level varies widely across studies, most of the reported percentages do not exceed 50% [ 24 ]. The level of inactivity is higher in older adults than in younger age groups [ 25 ], and people living in nursing homes or other residential care facilities seem to have even higher levels of inactivity than their community-dwelling counterparts [ 26 - 28 ]. Many people with dementia relocate to a nursing home, which implies they are at a higher risk of becoming sedentary.…”
Section: Introductionmentioning
confidence: 99%